Chemical synthesis of unique intermetallic TiFe nanostructures originating from the morphology of oxide precursors. Issue 18 (13th July 2021) - Kobayashi, Yasukazu; Teah, Heng Yi; Hanada, Nobuko
Abstract : TiFe nanostructures where prepared at temperatures as low as 600 °C with a Ti–Fe precursor and a CaH2 reducing agent in molten LiCl. For the first time an intermetallic compound with a unique layered morphology was found which could have originated from the FeTiO3 precursor. Abstract : In this study, intermetallic TiFe nanostructures were chemically prepared from Ti–Fe oxide precursors using a CaH2 reducing agent in molten LiCl at as low as 600 °C. The used precursor was spherical oxide nanoparticles or commercial FeTiO3 bulk powder. After the reduction treatment, the former precursor was changed to an aggregation of TiFe nanoparticles with a particle size of 44–46 nm. Surprisingly, the latter precursor was reduced to a layered morphology composed of TiFe nanoparticles with a particle size of 47–65 nm. An intermetallic compound with a unique layered morphology was found for the first time, and the layered morphology could have originated from the morphology of the FeTiO3 precursor in which the Fe 2+ and Ti 4+ ions occupied alternating layers perpendicular to the trigonal c -axis. The precursor originated morphology was enabled by the proposed low reduction temperature method, and the environment-friendliness of the proposed method was finally evaluated using life-cycle assessment (LCA).